2021
DOI: 10.1093/psyrad/kkab002
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental functional differences between gyri and sulci: implications for brain function, cognition, and behavior

Abstract: Folding of the cerebral cortex is a prominent characteristic of mammalian brains. Alterations or deficits in cortical folding are strongly correlated with abnormal brain function, cognition, and behavior. Therefore, a precise mapping between the anatomy and function of the brain is critical to our understanding of the mechanisms of brain structural architecture in both health and diseases. Gyri and sulci, the standard nomenclature for cortical anatomy, serve as building blocks to make up complex folding patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 235 publications
0
32
1
Order By: Relevance
“…For instance, the central sulcus separates the somatosensory cortex from the motor cortex, the calcarine sulcus separates the superior and inferior visual hemifields and even in the very complex and variable prefrontal cortices, the cortex sulcation influences the functional organization (Li et al, 2015 ; Lopez-Persem et al, 2019 ). In addition, functional differences (time-frequency activity, connectivity) exist between sulcal and gyral areas (Jiang et al, 2021 ).…”
Section: Cerebral Cortex Sulcationmentioning
confidence: 99%
“…For instance, the central sulcus separates the somatosensory cortex from the motor cortex, the calcarine sulcus separates the superior and inferior visual hemifields and even in the very complex and variable prefrontal cortices, the cortex sulcation influences the functional organization (Li et al, 2015 ; Lopez-Persem et al, 2019 ). In addition, functional differences (time-frequency activity, connectivity) exist between sulcal and gyral areas (Jiang et al, 2021 ).…”
Section: Cerebral Cortex Sulcationmentioning
confidence: 99%
“…Initial studies reported e.g., stronger disgust-related inferior frontal reactivity in women (Caseras et al, 2007), while other studies did not find sex differences (Baumann and Mattingley, 2012; Schienle et al, 2005a; Stark et al, 2003). Lastly, the present study included task-based fMRI studies focusing on regional analyses, while recent advanced approaches and findings suggest a distributed neural representation (Zhou et al, 2021) or a functional division between gyri and sulci (Jiang et al, 2015; Jiang et al, 2018; Jiang et al, 2021) of cognitive and emotional processes. Future studies may capitalize on these developments to further dissect common and differential neural representation of social and non-social processes or different defensive responses such as disgust and fear.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, correlations between functional specialization and anatomical properties have already been demonstrated using sulcal pattern as an anatomical landmark (Mangin et al, 2015;Jiang et al, 2021), with recent studies showing interesting population-wise tendencies. For example, an asymmetrical configuration of either the anterior cingulate cortex (inducing a more prominent paracingulate sulcus in the left hemisphere than in the right), or the inferior frontal sulcus's pattern (with one continuous and one interrupted, interdependently of the hemisphere) seem to be related to a better inhibitory control in children and adults (Tissier et al, 2019).…”
Section: Introductionmentioning
confidence: 87%
“…In parallel, correlations between functional specialization and anatomical properties have already been demonstrated using sulcal pattern as an anatomical landmark (Mangin et al, 2015;Jiang et al, . CC-BY-NC 4.0 International license made available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Introductionmentioning
confidence: 92%